A comprehensive study of the influence of the stoichiometry on the physical properties of TiO x films prepared by ion beam deposition - Marchi, María Claudia (2010)
A comprehensive study of nonstoichiometry titanium oxide thin films (TiO x , 0.3≤x≤2) prepared by ion beam deposition technique is reported. The physical properties of the material are studied by ultraviolet and x-ray photoelectron, Raman, and Fourier transform infrared spectroscopies, and atomic force microscopy. An abrupt transition from metallic characteristics to a wide gap semiconductor is observed in a very narrow range of oxygen variation. Concomitantly with this change the crystal structure and morphology suffer remarkable physical properties modifications. This transformation is ascribed to surface-volume energy minimization due to the influence of oxygen determining the size of the TiO 2 particles during coalescence.